FEM Simulation of a High-Performance 128°Y–X LiNbO3/SiO2/Si Functional Substrate for Surface Acoustic Wave Gyroscopes - Rui Ma; Weiguo Liu; Xueping Sun; Shun Zhou; Dabin Lin (Micromachines, 2022)
To obtain a high-performance surface acoustic wave (SAW) gyroscope substrate, the propagation characteristics and gyroscopic effect of Rayleigh waves in a 128°Y–X LiNbO3/SiO2/Si (LNOI) functional substrate were investigated with a three-dimensional finite element method. The influence of LNOI structural parameters on Rayleigh wave characteristics, including the phase velocity (vp), electromechanical coupling coefficient (K2) and temperature coefficient of frequency (TCF), were analyzed. The results demonstrate that the SiO2 layer compensates for the negative TCF of 128°Y–X LiNbO3 and enhances the K2 of the LNOI substrate. The Rayleigh wave velocity change of the LNOI substrate after rotations in different directions was studied. The gyroscope gain factor (η) represents the strength of the gyroscopic effect in the differential traveling wave SAW gyroscope and is defined. The ηy and ηz of the LNOI substrate with different structural parameters were investigated. Finally, an LNOI substrate with an hLN/λ of 0.2 and an hSiO2/λ of 0.05 was obtained by balancing the characteristic parameters, with a K2 of 3.96%, TCF of −18.75 ppm/°C and ηy of 0.26. The LNOI substrate has a better gyroscopic effect and temperature stability than the 128°Y–X LiNbO3 crystal. The LNOI substrate meets device miniaturization and integration needs.